Efficacy on pain and knee function of Kinesio taping among patients with patellofemoral pain syndrome: a systematic review and meta-analysis - Hailong Jiao; Meng Tao; Xianyou Cui (BMC Musculoskeletal Disorders)
Abstract Objective Kinesio taping (KT) has been widely used in patients with Patellofemoral pain syndrome (PFPS) because of its convenience and positive effects. However, there exists conflicting evidence regarding its efficacy. To systematically evaluate the effect of KT on pain and knee function in patients with PFPS. Methods This study was registered in PROSPERO (registration number CRD 42023442333) and completed following the PRISMA checklist. This study did not receive any funding. PubMed, Embase, The Cochrane Library, Web of Science, and EBSCO databases were comprehensively searched by two independent reviewers following PRISMA guidelines for the inclusion of randomized controlled trials (RCTs) exploring the effects of KT on pain and knee function in patients with PFPS. Quality assessment was evaluated using the Cochrane Risk Assessment Scale. Statistical analysis was performed using Review Manager 5.3. Results Ten RCTs published from 2011 to 2022 were included in this review. A total of 364 PFPS patients were analyzed, with 184 in the KT group and 180 in the control group. The KT group primarily received KT plus routine rehabilitation, while the control group received routine rehabilitation alone. The overall quality of the included studies was relatively low. Meta-analysis showed that KT significantly reduced visual analog scale pain scores (MD=-0.58, 95% CI: -1.10 to -0.07, P = 0.03) and increased the Kujala anterior knee pain scale score (MD = 2.28, 95% CI: 0.00 to 4.56, P = 0.05) in patients with PFPS compared with controls. While knee extension peak torque (SMD = 0.06, 95% CI: -0.39 to 0.52, P = 0.79), knee flexion peak torque (SMD = 0.36, 95% CI: -0.28 to 0.99, P = 0.27), knee flexion range of motion (MD=-0.93, 95% CI: -4.54 to 2.68, P = 0.61), and knee joint position error (MD=-0.48, 95% CI: -1.91 to 0.96, P = 0.51) were not significantly different among KT and control groups. Conclusion Current evidence suggests that Kinesio taping reduces pain in patients with patellofemoral pain syndrome, but its effects on knee muscle strength, knee flexion range of motion, and knee proprioception need further investigation. Given its low cost and accessibility, Kinesio taping can be used for pain management in patellofemoral pain syndrome.